Nonengraftment Haploidentical Cellular Therapy for Hematologic Malignancies - John L. Reagan; Loren D. Fast; Eric S. Winer; Howard Safran; James N. Butera; Peter J. Quesenberry (Advances in Hematology)
Much of the therapeutic benefit of allogeneic transplant is by a graft versus tumor effect. Further data shows that transplant engraftment is not dependant on myeloablation, instead relying on quantitative competition between donor and host cells. In the clinical setting, engraftment by competition alone is not feasible due to the need for large numbers of infused cells. Instead, low-level host irradiation has proven to be an effective engraftment strategy that is stem cell toxic but not myeloablative. The above observations served as the foundation for clinical trials utilizing allogeneic matched and haploidentical peripheral blood stem cell infusions with minimal conditioning in patients with refractory malignancies. Although engraftment was transient or not apparent, there were compelling responses in a heavily pretreated patient population that appear to result from the breaking of tumor immune tolerance by the host through the actions of IFNγ, invariant NK T cells, CD8 T cells, NK cells, or antigen presenting cells.